THE DYNAMICS OF THE SAMBAS SULTANATE DURING THE REIGN OF SULTAN MUHAMMAD ALI TSAFIUDDIN (1815–1828): DINAMIKA KESULTANAN SAMBAS PADA MASA SULTAN MUHAMMAD ALI TSAFIUDDIN (1815–1828) - Nuraidi Nuraidi; Andang Firmansyah; Prabowo M. Rikaz (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the political and social dynamics of the Sambas Sultanate during the reign of Sultan Muhammad Ali Tsafiuddin (1815–1828), focusing on the challenges to sovereignty faced by the sultanate in the early nineteenth century. The research employs the historical method, including topic selection, source collection (heuristics), source criticism (verification), interpretation, and historiographical writing, combined with political and sociological approaches to analyze power relations and regional contexts. The findings show that the sultan’s reign occurred during a period of significant transformation marked by increasing Dutch colonial intervention and internal instability arising from conflicts among Chinese mining kongsis. These pressures gradually weakened the authority of the sultanate and limited the effectiveness of traditional governance. In response, Sultan Muhammad Ali Tsafiuddin pursued strategic measures aimed at maintaining political stability while adapting to shifting regional power structures.This study argues that the erosion of the Sambas Sultanate’s sovereignty resulted not only from colonial expansion but also from internal socio-economic dynamics. The research thus contributes to the historiography of West Kalimantan by highlighting the complex interactions between local authority, economic communities, and colonial power in the nineteenth century.